2021
DOI: 10.18844/cjes.v16i3.5823
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Edmodo in writing: A conceivable course of fusion

Abstract: A problem that still persists in Collaborative Writing is the lack of use of relevant technology to counter lessened interaction and learning participations in developing writing skills effectively.  To offset these difficulties, this study examines the use of Edmodo on students' collaborative writing. This study used a quasi-experimental study of 56 students, grade 10, Gresik, Indonesia, with two assigned classes of experimental and the control group, each containing of 28 students. The results of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
2
6
0
1
Order By: Relevance
“…Further analysis revealed that among four subcomponents of writing accuracy, the subcomponent grammar witnessed a significant improvement (p<.05). The results of this research are in line with the findings of various researchers (e.g., Anwar, 2021;Miftah & Raya, 2018) who proved the effectiveness of Edmodo in EFL writing class.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Further analysis revealed that among four subcomponents of writing accuracy, the subcomponent grammar witnessed a significant improvement (p<.05). The results of this research are in line with the findings of various researchers (e.g., Anwar, 2021;Miftah & Raya, 2018) who proved the effectiveness of Edmodo in EFL writing class.…”
Section: Discussionsupporting
confidence: 90%
“…Internet-based learning media, such as wikis and blogs has merged with writing for optimal interaction and cognitive development (Talib & Cheung, 2017). Some researchers' (Anwar, 2021;Li, 2015) studies have suggested that technology-mediated tools encourage collaborative writing and develop the quality of writing. In addition, a significant number of students had a positive attitude towards implementing online collaborative tasks (Wang, 2009).…”
Section: Effects Of Collaboration On Writing Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…The data shows that the average students' scores reflect a high understanding level, indicating the students' success in comprehending the basic principles of descriptive texts. This result aligns with previous research that suggests a sound theoretical understanding is the first key to writing descriptive texts well (Anwar, 2021;Asrifan et al, 2020;Chen, 2021;Mauludin et al, 2021;Yamin & Setiawan, 2019;Yemelyanova et al, 2022).…”
Section: Student Learning Activity Evaluationsupporting
confidence: 92%
“…Peserta didik harus terbiasa dengan tanda baca seperti titik, koma, titik dua, titik dua, tanda hubung, dan huruf besar (Turmudi, 2020). Selain itu, ada empat kesulitan dasar menulis bagi penulis pemula, kesulitan yang paling sering terjadi adalah penggunaan bahasa, koherensi, dan kohesi serta memilih topik yang signifikan dan referensi yang relevan (Anwar, 2021a). Sebaliknya, parafrase, referensi, dan kutipan adalah yang paling tidak bermasalah.…”
Section: Pendahuluanunclassified